IMPLEMENTATION OF CHARACTER EDUCATION ON STUDENTS’ HONESTY IN STATE ELEMENTARY SCHOOL KALIBOYO BATANG - Abdul Khobir; Martina Septi Manisa; Mei Yuniati (Auladuna: Jurnal Pendidikan Dasar Islam, 2022)
This study aimed to determine the implementation of character education on students’ honesty and find its supporting and inhibiting factors. The method used was quantitative descriptive. The research participants were 32 students from classes V and VI of State Elementary School Kaliboyo, selected using purposive sampling. The instruments were an observation sheet and a questionnaire. Data were analyzed using quantitative analysis. The results indicated that character education in fostering students’ honesty used several indicators, such as the teachers reminding students not to cheat, reporting school activities transparently, and having an honest student recruitment system. Habituation also needed to implement, such as the habituation of 6R (Concise, Clean, Neat, Diligent, Caring, and Friendly), the habituation of 5S (Smile, Greetings, Greetings, Polite, and Courtesy), and donating habituation. Besides, the factors that influenced the implementation of character education in fostering the honesty of State Elementary School Kaliboyo were teachers as role models, students themselves, guardians/family, and the school discipline system. At the same time, the inhibiting factor was unsupporting environments.